Compensation, Benefits, and Work Motivation Effects on Hotel Employee Performance: The Mediating Role of Job Satisfaction - Lina Kartikaningrum (CV. Satria Jaya, 2025)
This study aims to examine the effect of compensation, benefits, and work motivation on employee performance with job satisfaction as a mediating variable among hotel employees in Batu City, East Java. The research employed a quantitative approach with a survey method. The population consisted of 450 employees from 15 four-star and five-star hotels in Batu City. Using purposive sampling technique, 210 respondents were selected based on minimum one-year tenure criteria. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 3.0 software. The results indicated that compensation, benefits, and work motivation significantly influence employee performance both directly and indirectly through job satisfaction as a mediating variable. This study contributes to human resource management literature by providing empirical evidence on the importance of integrated compensation and benefit strategies in the hospitality industry, particularly in tourism cities.